2007
DOI: 10.1080/07362990601139669
|View full text |Cite
|
Sign up to set email alerts
|

A Delayed Black and Scholes Formula

Abstract: In this article we develop an explicit formula for pricing European options when the underlying stock price follows a non-linear stochastic functional differential equation. We believe that the proposed model is sufficiently flexible to fit real market data, and is yet simple enough to allow for a closed-form representation of the option price. Furthermore, the model maintains the completeness of the market. The derivation of the option-pricing formula is based on an equivalent martingale measure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
125
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 134 publications
(130 citation statements)
references
References 20 publications
0
125
0
Order By: Relevance
“…As a result, the discounted asset price process e −rt S(t) is a martingale and the model is arbitrage-free. The uniqueness of the equivalent martingale measure guarantees that the market is complete and therefore appropriate hedging strategies can also be obtain, for more details see Arriojas et al [3]. Hobson & Rogers [13] also observed that their model produces the right smiles and skews in the resulting implied volatility plots as in Figure 1.…”
Section: A Complete Market Model With a Smilementioning
confidence: 82%
See 4 more Smart Citations
“…As a result, the discounted asset price process e −rt S(t) is a martingale and the model is arbitrage-free. The uniqueness of the equivalent martingale measure guarantees that the market is complete and therefore appropriate hedging strategies can also be obtain, for more details see Arriojas et al [3]. Hobson & Rogers [13] also observed that their model produces the right smiles and skews in the resulting implied volatility plots as in Figure 1.…”
Section: A Complete Market Model With a Smilementioning
confidence: 82%
“…It is here where one can observe a link between Arriojas et al [3] and Hobson & Rogers [13] since both approaches require the same structure for the unique (in each case) equivalent martingale measure dP dP := exp…”
Section: A Complete Market Model With a Smilementioning
confidence: 99%
See 3 more Smart Citations